Efektivitas Pelatihan Regulasi Emosi Untuk Meningkatkan Sikap Anti Bullying Pada Siswa SMP - Sa'adah, Miftahul Aula (2016)
Cases of violence occur in the school environment. One is bullying. Most bullies are emotionally unstable. Cases of bullying that goes on continuously and sustainably have a very negative effect that the need for effective solutions to mitigate them. Such a solution could be training in emotion regulation. The purpose of this study was to test the effectiveness of the training of emotion regulation to improve anti-bullying stance on private junior high school students A. This research method using quasi-experimental research with the model of pretest-posttest control group design. Subjects were students in grade 2 junior A Private totaling 30 people (15 experimental group and 15 control group). The analysis was performed with non-parametric statistical test by Mann Whitney U test is to compare the experimental group and the control group, the value of post test Z = -4.688; sig = 0.000 (p <0.01) and the value of follow-up was obtained value of Z = -4.673; sig = 0.000 (p <0.01). Furthermore, the results of test analysis Wilxocon in the experimental group before and after the training with a significant level of emotion regulation obtained pretest-posttest Z value of -3.408 (sig = 0.001); p <0.05. This means that the hypothesis is accepted. This means that there is an increase in anti-bullying stance significantly in the experimental group were given training of emotion regulation. This means, emotion regulation training is effective in improving anti-bullying stance. The findings in this study is the subject of bullying research actions due to a lack of understanding about bullying and what do they think only joking and reasonable committed by children their age.